Ruminations on Literature in a Globalised Context - Rahul Peter Das (Ksiegarnia Akademicka Publishing, 2021)
A critical appraisal of the term and concept of “world/global literature,” examining inter alia the two opposing notions of particularity and commonality/universality associated with it, the issue of selection and who has the authority to select, and the problem of the language interface.